2021
DOI: 10.1109/jstsp.2020.3037485
|View full text |Cite
|
Sign up to set email alerts
|

On Filter Generalization for Music Bandwidth Extension Using Deep Neural Networks

Abstract: In this paper, we address a sub-topic of the broad domain of audio enhancement, namely musical audio bandwidth extension. We formulate the bandwidth extension problem using deep neural networks, where a band-limited signal is provided as input to the network, with the goal of reconstructing a fullbandwidth output. Our main contribution centers on the impact of the choice of low pass filter when training and subsequently testing the network. For two different state of the art deep architectures, ResNet and U-Ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…The performance of BWE models is highly sensitive to different anti-aliasing filters when downsampling methods in testing differ from training [5,6,10]. Similar to [10], to improve the robustness of our model, we generate the low-rate signals by downsampling the high-rate speech dataset with random anti-aliasing filters. More specifically, we adopt the Chebyshev Type I anti-aliasing filter and randomize its ripple and order parameters.…”
Section: Improving Robustness To Downsampling Methods By Augmentationmentioning
confidence: 99%
See 3 more Smart Citations
“…The performance of BWE models is highly sensitive to different anti-aliasing filters when downsampling methods in testing differ from training [5,6,10]. Similar to [10], to improve the robustness of our model, we generate the low-rate signals by downsampling the high-rate speech dataset with random anti-aliasing filters. More specifically, we adopt the Chebyshev Type I anti-aliasing filter and randomize its ripple and order parameters.…”
Section: Improving Robustness To Downsampling Methods By Augmentationmentioning
confidence: 99%
“…In addition, training endto-end BWE models requires high-rate target signals, making valuable low-rate data collected from telephony 8-kHz infrastructure unusable. It has also been observed that BWE models are susceptible to low-pass filtering [6,10], generating severe distortion at the transition band of the anti-aliasing filter. This problem can be mitigated by data augmentation [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, when microphones have low responses in high-frequency, or audio recordings are compressed to low sampling rates, the high frequencies information will be lost. We follow the description in to produce low-resolution distortions but add more filter types (Sulun & Davies, 2020). After designing a low pass filter h, we first convolve it with s to avoid the aliasing phenomenon.…”
Section: Introductionmentioning
confidence: 99%